Suitability of the In Vitro Cytokinesis-Block Micronucleus Test for Genotoxicity Assessment of TiO2 Nanoparticles on SH-SY5Y Cells - Fernández-Bertólez, Natalia (2022)
(This article belongs to the Special Issue Toxicity of Nanomaterials and Legacy Contaminants: Risks to the Environment and Human Health)